The effect of initial treatment on hearing prognosis in idiopathic sudden sensorineural hearing loss: a nationwide survey in Japan. (10th March 2017) - Okada, Masahiro; Hato, Naohito; Nishio, Shin-ya; Kitoh, Ryosuke; Ogawa, Kaoru; Kanzaki, Sho; Sone, Michihiko; Fukuda, Satoshi; Hara, Akira; Ikezono, Tetsuo; Ishikawa, Kotaro; Iwasaki, Satoshi; et al.
Abstract: Objective: To investigate the hearing prognosis of idiopathic sudden sensorineural hearing loss (SSNHL) treated with different initial therapies. Methods: Subjects consisted of patients diagnosed with idiopathic SSNHL within 7 days from onset and showing severe hearing loss (≥60 dB), who were registered in a Japanese multicenter database between April 2014 and March 2016. Subjects were divided into four groups according to initial therapy: (1) steroids, (2) steroids + Prostaglandins (PGs), (3) intratympanic steroids (ITS), and (4) no steroids. Hearing outcomes were compared among the groups. Results: In total, 1305 patients were enrolled. The final hearing level and hearing gain of patients treated with steroids + PGs were significantly higher than those of patients treated with steroids alone or no steroids. The ratio of good prognosis (complete recovery or marked improvement) in patients treated with steroids + PGs was higher than that in patients treated with steroids alone or no steroids. There was no difference in the prognosis of patients treated with steroids alone or no steroids. Conclusion: A large number of patients with idiopathic SSNHL were registered in a multicenter database. PG use in combination with steroid administration was associated with a good hearing prognosis in patients with severe hearing loss.